Antecedents of HR Influencing Employee Performance: Mediating Effect of Firms’ Agility - Sharmin, Jinia Afroz; Rashid, Azmain Bin (Jahangirnagar University Journal of Management Research, 2023)
The efficient performance of employees is essential for the success of any firm, and this performance is affected by factors such as HR analytics, merit-based payment, and HR involvement. The study focuses on the pharmaceutical industry in Bangladesh and aims to examine the impact of these factors on employee performance efficiency. The study uses a structured questionnaire to collect data from 119 responses and analyzes the data using Smart PLS version 3.3.3. The results suggest that HR analytics, merit-based payment, and HR involvement significantly impact employee performance efficiency. Additionally, this research discovers that the agility of a firm acts as a mediator in the connection between HR analytics and employee performance, as well as between HR involvement and employee performance but there is no influence of merit-based payment on firm’s agility. This study highlights the importance of effective HR management in promoting employee performance efficiency and ultimately contributing to the success of the firm. Notably, this study focuses solely on three prevalent HR factors of influence. Introducing additional HR factors could potentially yield significantly different outcomes, an avenue for future exploration.